2004
DOI: 10.1083/jcb.200405130
|View full text |Cite
|
Sign up to set email alerts
|

TSC2 modulates actin cytoskeleton and focal adhesion through TSC1-binding domain and the Rac1 GTPase

Abstract: Tuberous sclerosis complex (TSC) 1 and TSC2 are thought to be involved in protein translational regulation and cell growth, and loss of their function is a cause of TSC and lymphangioleiomyomatosis (LAM). However, TSC1 also activates Rho and regulates cell adhesion. We found that TSC2 modulates actin dynamics and cell adhesion and the TSC1-binding domain (TSC2-HBD) is essential for this function of TSC2. Expression of TSC2 or TSC2-HBD in TSC2−/− cells promoted Rac1 activation, inhibition of Rho, stress fiber d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
128
6
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(149 citation statements)
references
References 51 publications
12
128
6
3
Order By: Relevance
“…There are two functionally distinct mTOR complexes, mTORC1, responsible for cell growth and proliferation, and mTORC2, which signals through Rho GTPases to stimulate actin stress fiber formation [31]. TSC2 can also inhibit Rho by binding to TSC1, and thus promote stress fiber disassembly and focal adhesion remodeling [23]. Therefore, AMPK modulates substrates that potentially control actin stress fiber dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…There are two functionally distinct mTOR complexes, mTORC1, responsible for cell growth and proliferation, and mTORC2, which signals through Rho GTPases to stimulate actin stress fiber formation [31]. TSC2 can also inhibit Rho by binding to TSC1, and thus promote stress fiber disassembly and focal adhesion remodeling [23]. Therefore, AMPK modulates substrates that potentially control actin stress fiber dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been best characterized as a controller of cell size through its regulation of ribosomal synthesis proteins including ribosomal S6 kinase (17,18), TSC2 has been implicated in a number of related signaling pathways in a variety of cell types (19). Investigations of Madin-Darby canine kidney epithelial cells demonstrated that overexpression of TSC2 results in activation of Rho and increased cellular motility (15), and analysis of TSC2-deficient cells has shown reduced Rho activity (16), although these effects may depend on the cell type investigated (20). Although mutational inactivation of TSC2 contributes to tuberous sclerosis complex, regulation of intact TSC2 occurs principally through the action of the serine͞threonine kinase Akt1͞protein kinase B (21,22).…”
mentioning
confidence: 99%
“…Tsc2 modulates actin dynamics, inducing a cortical F-actin distribution and regulating RhoA activity (16). A subset of key downstream transcriptional targets, including forkhead ligand1 (FKHR-L1), MDM2, BAD, Huntington, and arfaptin2, are phosphorylated by Akt (17).…”
mentioning
confidence: 99%